DIEP Flap Transplantation in Monozygotic Twins for Breast Reconstruction: A Case Report and Literature Review - Ozturk, Cemile Nurdan; Manisundaram, Arvind D.; Rivera, Mariangela; Ozturk, Can; Moon, Wong (Journal of Reconstructive Microsurgery Open, 2023)
Background Composite tissue allotransplants are performed for various defects when local, or distant reconstructive options are limited. Though this type of transplant replaces similar tissue, it is complicated by immunosuppression. This limitation may be avoided in monozygotic twins since they share identical genetic code. Free soft tissue transplantation across identical twins has been reported for breast, scalp, and thoracic reconstruction when autologous tissues were insufficient. We present a case of a successful deep inferior epigastric artery perforator (DIEP) flap transplantation in monozygotic twins.Methods The recipient twin was a patient with history of breast cancer and failed prosthetic reconstruction. She desired autologous reconstruction with a DIEP flap but had insufficient donor tissue. She refused alternative sites; however, she had an identical twin willing to donate her excess abdominal tissue. The twins underwent deoxyribonucleic acid testing, human leukocyte antigen/blood type testing, and screening for communicable diseases.Results The twins were found to have greater than 99.99% probability of being monozygotic twins. A bipedicled conjoined DIEP was harvested from donor twin and transplanted to recipient twin. Immunosuppressive regimen was not utilized. Patients healed uneventfully and are currently 5 years postop without long-term complications.Conclusion Isogeneic flap transplant is a viable option to consider when autologous tissues are restricted, and monozygotic twins are present. Appropriate counseling of twins is critical for a successful and satisfactory outcome.
Keywords: twin transplantation; soft tissue transplantation; breast reconstruction; flap transplantation; DIEP transplantation